Luminescent perovskite nanocrystal composites via in situ ligand polymerization towards display applications. Issue 41 (8th October 2021) - Zhou, Jun; Fang, Fan; Chen, Wei; Mei, Ming; Liu, Peizhao; Hao, Junjie; Tang, Haodong; Liang, Suzhe; Lei, Wei; Pan, Ruikun; Cheng, Jiaji; Müller-Buschbaum, Peter; et al.
Abstract : Herein we introduce an in situ ligand polymerization (ILP) method for the fabrication of PeNC composites with intrinsic hydrophobic surface and optimized composite morphology. The composites exhibit great potential for advanced display applications. Abstract : Luminescent inorganic perovskite nanocrystals (PeNCs) are promising in various optical applications, particularly in advanced lighting and displays. The instability of PeNCs and PeNC composites from different aspects hinder their practical applications. Many previous methods indicate that an intact and facile wrapping strategy could effectively address this challenge. In this work, we introduce an in situ ligand polymerization (ILP) method for the fabrication of PeNC composites. By introducing (3-aminopropyl)triethoxysilane (APTES) as the initial ligand of the PeNCs directly and polymethylhydrosiloxane (PMHS) as the monomer to form the polymerized matrix, a polymerized and hydrophobic SiO2 matrix structure is formed, which intrinsically protects the PeNCs against moisture-induced deterioration. The stability test indicates that the ILP composite powders demonstrate an improved stability against various solvent conditions and light exposure compared to the conventional PeNCs–SiO2 composite. More importantly, the ILP composite exhibits an excellent compatibility with the acrylate solvent which is widely used for light-solidification in light converting film fabrication. The ILP composite film demonstrates an ultrastable operational performance in our standard test outperforming the conventional PeNCs–SiO2 composite configuration. Thus, the ILP composite demonstrates great potential for use in advanced lighting and displays.